2017
DOI: 10.2298/gensr1702495s
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of characteristics in barley cultivars

Abstract: Knowledge of the genetic diversity is important to design appropriate selection criteria in the breeding programs. In this study, the genetic diversity of 42 Iranian and European barley cultivars was investigated with morpho-agronomic traits including phenological, physiological, morphological traits, grain yield and associated traits. Analysis of variance showed high variability among cultivars. The European cultivars Panaka, Aiace and Pariglia had the highest grain yield. The results of group comparisons ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
2
7
0
1
Order By: Relevance
“…Also, the five promising wheat hybrids mentioned above were recorded highly significant and positive results of heterosis over better parent, and they were very distinguished concerning the incident superiority for SCA effects which indicates that these genotypes are the actual nucleus for producing salinity tolerance wheat lines in addition, high yielding in this regard. Results of Bi-plot analysis were in good harmony with Dehghani et al (2012), Saroei et al (2017), Mariey et al (2021), who reported that the hierarchical cluster and Bi-plot analysis based on phenotypic traits were aimed to detect homogeneous groups with large heterogeneity among them. Also, they are considered a valuable tool for subdividing the number of genotypes in groups including similarity and dissimilarity genotypes, to help the breeder plan an effective breeding program.…”
Section: Discussionsupporting
confidence: 68%
“…Also, the five promising wheat hybrids mentioned above were recorded highly significant and positive results of heterosis over better parent, and they were very distinguished concerning the incident superiority for SCA effects which indicates that these genotypes are the actual nucleus for producing salinity tolerance wheat lines in addition, high yielding in this regard. Results of Bi-plot analysis were in good harmony with Dehghani et al (2012), Saroei et al (2017), Mariey et al (2021), who reported that the hierarchical cluster and Bi-plot analysis based on phenotypic traits were aimed to detect homogeneous groups with large heterogeneity among them. Also, they are considered a valuable tool for subdividing the number of genotypes in groups including similarity and dissimilarity genotypes, to help the breeder plan an effective breeding program.…”
Section: Discussionsupporting
confidence: 68%
“…In view of these circumstances, the financial analyses showed that poultry feed mills were highly profitable from the view point of individual investments. This research is also supported by some research like feed costs typically represent the highest cost item in smallholder production systems, implying that both quantity and quality of feed have a significant effect in determining profitability [25,26].…”
Section: Profitability Analysis Of Broiler Productionsupporting
confidence: 57%
“…RAPD profile is easy, unlimited marker numbers, fast and efficient technique. Thus, it is widely used for determining genetic variation among barley varieties (Tanyolac et al, 2003;Raoudha et al, 2010 andSaroei et al,2017).The use of biochemical and modern molecular markers to identify genotypic variation between barley genotypes is an important step toward effective and specific strategies for breeding program. Thus, the target from this study was to determine the genetic diversity among some Egyptian barley cultivars based on the genetic distances obtained from SDS-PAGE and RAPD-PCR markers.…”
Section: Introductionmentioning
confidence: 99%